An improved and broadly accurate local approximation to the exchange–correlation density functional: The MN12-L functional for electronic structure calculations in chemistry and physics - Peverati, Roberto; Truhlar, Donald G. (Physical chemistry chemical physics : PCCP, 2012)
We report a new local exchange-correlation energy functional that has significantly improved across-the-board performance, including main-group and transition metal chemistry and solid-state physics, especially atomization energies, ionization potentials, barrier heights, noncovalent interactions, isomerization energies of large moleucles, and solid-state lattice constants and cohesive energies.